Composición nutricional y anti nutricional de la estructura del bledo manso (Amaranthus dubius) - Rosado Alcívar, Priscilla Mariana (2024)
This study evaluated the nutritional and anti-nutritional composition profiles of different parts of the Bledo Manso (Amaranthus dubius), as well as the elaboration and sensory evaluation of cookies based on flour from its seeds using the Design Thinking tool. A completely randomized experimental design (DCA) was used and it was found that fiber varied significantly among the different parts of the plant, ranging from 4.36% to 30.16%, being the stem and root the ones that stood out with the highest levels. Fat content was found exclusively in the seeds with a percentage of 0.46%, while protein varied between 1.00% and 17.76% in the different parts of the plant. A gum level of 9.12% was found in the seeds and waxes in the leaves of 1.28% and in the stem of 0.17%. Toxicity index analysis showed that the seeds of Bledo Manso showed no agglutination, while the leaves, stem and root showed agglutination easily in fine particles. Sensory analysis showed a generally positive acceptability in terms of color, odor, flavor and texture of the cookies produced, supporting their potential as a satisfactory option for the identified target market. In conclusion, with this information, it will be possible to establish the nutritional capacity of the Bledo Manso (Amaranthus dubius) and its potential as a food for human or animal consumption.